Fragmented sovereignty and legal pluralism in Sri Lanka: Reconfiguring state authority after the 2022 economic crisis - Shuhood, Fathima Adila; Marah, Thomas Sheku (Privietlab, 2026)
In April 2022, Sri Lanka became the first South Asian state to default on its external debt in the post-independence period, triggering severe economic disruption, mass political protests, emergency governance measures and extensive intervention by international financial institutions. Beyond its fiscal dimensions, the crisis has produced a significant reconfiguration of state authority and legal governance. Existing scholarship has largely examined the crisis through political economy and macroeconomic frameworks, while insufficiently addressing how crisis governance reshapes the organization of sovereignty through interactions between domestic legal systems and transnational regulatory regimes. This study examines how the 2022 economic crisis redistributed legal and institutional authority across executive institutions, plural legal orders, and externally conditioned governance frameworks in Sri Lanka. Employing a qualitative case study design, the analysis draws on constitutional provisions, emergency regulations, fiscal reform legislation, International Monetary Fund (IMF)-linked policy frameworks, and institutional practices between 2022 and 2025. The findings demonstrate that crisis governance generated a fragmented structure of authority in which executive consolidation, externally embedded fiscal conditionalities, and strategic uses of legal pluralism became the central mechanisms of governance. This article conceptualizes this configuration as fragmented sovereignty, defined as the structured dispersion of authority across overlapping domestic and transnational legal regimes. This study contributes to debates on sovereignty, legal pluralism, and global governance by demonstrating how an economic crisis transforms the internal organization of state authority in postcolonial contexts. The findings highlight the governance risks associated with externally conditioned crisis reforms, including weakened accountability, regulatory inconsistency, and reduced transparency in public decision-making.